Prevalence and duration of breast milk feeding in very preterm infants: A 3-year follow-up study and a systematic literature review - Rodrigues, C (2018)
Background: The World Health Organization recommends exclusive breast milk feeding until 6 months and continuing up to 2 years of age; little is known about whether very preterm infants are fed in accordance with these recommendations. We aimed to describe the prevalence and duration of breast milk feeding in very preterm children and to systematically review internationally published data. Methods: We evaluated breast milk feeding initiation and duration in very preterm children born in 2 Portuguese regions (2011‐2012) enrolled in the EPICE cohort and followed‐up to the age of 3 (n = 466). We searched PubMed® from inception to January 2017 to identify original studies reporting the prevalence and/or duration of breast milk feeding in very preterm children. Results: 91.0% of children received some breast milk feeding and 65.3% were exclusively breast fed with a median duration of 2 months for exclusive and 3 months for any breast milk; only 9.9% received exclusive breast milk for at least 6 months, 10.2% received any breast milk for 12 months or more, and 2.0% for up to 24 months. The literature review identified few studies on feeding after hospital discharge (n = 9); these also reported a low prevalence of exclusive breast milk feeding at 6 months (1.0% to 27.0%) and of any breast milk at 12 months (8.0% to 12.0%). Conclusions: The duration of breast milk feeding among Portuguese very preterm infants was shorter than recommended. However, this appears to be common globally. Research is needed to inform strategies to promote continued breast milk feeding.